Analysis of the Financial Literacy Behavior Model - Kartini, K.; Fitri, Fitri; Rabiyah, Ulfa; Anggraeni, Dewi (Golden Ratio of Finance Management, 2021)
Financial literacy is a combination of awareness, knowledge, abilities, attitudes, and behaviors needed to make financial decisions. This study aims to find a behavioral model of financial literacy. This study uses a survey method with a quantitative approach. Respondents involved homemakers in Maros Regency, South Sulawesi, to fill out the questionnaire provided. Path Analysis was used to analyze the data SPSS and Winistep are used as tools in analyzing the data. Specifically, the data analysis used in this study used Structural Equation Modeling (SEM) data analysis techniques. Statistically, the value of the sample covariance matrix must not differ significantly from the population covariance matrix value. Financial Literacy Attitudes had a direct effect on Financial Literacy Behavior. Basic Knowledge of Financial Literacy had a direct effect on Financial Literacy Behavior. Financial literacy behavior is determined by financial literacy attitudes and basic financial literacy knowledge. Therefore, financial literacy knowledge and attitudes need to be improved to improve financial literacy behavior among homemakers. Financial Literacy Attitudes contribute the most to financial literacy factors. financial attitudes that have a more significant influence on financial knowledge in financial management practices.